2019
DOI: 10.1590/1806-9061-2019-1100
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Investigations of the Effect of Thermal Manipulation During Embryogenesis on Body Performance and Structure of Pectoral and Thigh Muscle of Ross Broiler Chicken

Abstract: The aim of this study was to determine the optimum timing of thermal manipulation during early, mid, late and long lasting embryogenesis that may result in improvement of body performance and myofiber development (fiber diameter and thickness of perimysium) of pectoral and thigh muscles by a comparative morphometrical investigation on post-hatch day 35. 1440 fertile Ross broiler eggs were divided randomly and equally into 5 treatment groups: control (no TM), TM1, TM2 TM3 and TM4 were thermally subjected to 39º… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…The effect of TM on hatchability in the present review is contradictive, with 65% of 20 studies that reported hatchability found no significant effect, 30% being reduced, and a comparative study by Dalab and Ali [46] reported increased and decreased hatchability with intermittent TM at different embryonic age. Also, earlier studies regarding TM and hatchability have shown contradicting results, for instance, Yahav et al [11] and Piestun et al [22] reported significantly increased hatchability with TM at 39.5°C for 3 h/d from E8 to E10 and 38.1°C for 24 h/d from E0 to E5, respectively.…”
Section: Thermal Manipulation and Hatchabilitycontrasting
confidence: 82%
See 3 more Smart Citations
“…The effect of TM on hatchability in the present review is contradictive, with 65% of 20 studies that reported hatchability found no significant effect, 30% being reduced, and a comparative study by Dalab and Ali [46] reported increased and decreased hatchability with intermittent TM at different embryonic age. Also, earlier studies regarding TM and hatchability have shown contradicting results, for instance, Yahav et al [11] and Piestun et al [22] reported significantly increased hatchability with TM at 39.5°C for 3 h/d from E8 to E10 and 38.1°C for 24 h/d from E0 to E5, respectively.…”
Section: Thermal Manipulation and Hatchabilitycontrasting
confidence: 82%
“…Studies by Zaboli et al [41], Al-Zghoul et al [45], and Dalab and Ali [46] reported depressed embryo, hatch, or chick weight due to intermittent high-temperature TM, which partially agrees with Piestun et al [14]. However, Piestun et al [14] reported that only continuous (24 h) elevation in incubation temperature (39.5°C) from E7 to E16 negatively affected embryo growth and development and hatch weight.…”
Section: Thermal Manipulation and Embryo Hatch Or Chick Weightmentioning
confidence: 62%
See 2 more Smart Citations
“…In the current study, TM was achieved by raising the incubation conditions to 39 • C and 65% RH for 18 h/day from ED 10 to 18. Previous studies used similar TM treatment parameters, including incubation at 39 • C for 18 h/day from ED 7-11, at 38.5 • C from ED 16 to 18 and at 39 • C for 18 h/day from ED 12 to 18, and these parameters were shown to significantly enhance BW as well as upregulate expression of muscle marker genes [27,[31][32][33]. The duration of TM was reported to affect thermotolerance acquisition in broilers, and different TM treatments led to differences in physiological parameters as well as varied mRNA expression profiles of heat shock genes [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%